2007
DOI: 10.1194/jlr.m600266-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Anti-bis(monoacylglycero)phosphate antibody accumulates acetylated LDL-derived cholesterol in cultured macrophages

Abstract: Bis(monoacylglycero)phosphate (BMP), also called lysobisphosphatidic acid, is a phospholipid highly enriched in the internal membranes of multivesicular late endosomes, in which it forms specialized lipid domains. It has been suggested that BMP-rich membranes regulate cholesterol transport. Here, we examine the effects of an anti-BMP antibody on cholesterol metabolism and transport in two macrophage cell lines, RAW 264.7 and THP-1, during loading with acetylated low density lipoprotein (AcLDL). Anti-BMP antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…This indicates that BMP synthesized from exogenous PG is specifically located in late endosomes, similar to endogenous BMP (1,3). We may then assume that supplementation of RAW macrophages with 18:1/18:1-PG increases BMP content without altering its stereoconfiguration and cellular location, providing an alternative approach to the anti-BMP antibody or drugs such as D-threo-1-phenyl-2-decanoylamino-3-morpholino-1-propanol (8,12) to investigate the functions of BMP in cellular models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that BMP synthesized from exogenous PG is specifically located in late endosomes, similar to endogenous BMP (1,3). We may then assume that supplementation of RAW macrophages with 18:1/18:1-PG increases BMP content without altering its stereoconfiguration and cellular location, providing an alternative approach to the anti-BMP antibody or drugs such as D-threo-1-phenyl-2-decanoylamino-3-morpholino-1-propanol (8,12) to investigate the functions of BMP in cellular models.…”
Section: Discussionmentioning
confidence: 99%
“…BMP is involved in the formation of the multivesicular membrane organization of late endosomes (4,5). It has been suggested that BMP participates in the trafficking of lipids and proteins, particularly cholesterol, through late endosomes (6)(7)(8). Recent studies have indicated that the ability of the endosomal Niemann-Pick C2 protein to transfer cholesterol to PL vesicles is increased by the presence of BMP (9,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was then shown to be enriched in lysosomes of the rat liver (2) and in alveolar macrophages (3) and reported to accumulate in lipid storage diseases and drug-induced lipidosis (4)(5)(6). Recently, it was demonstrated that this peculiar phospholipid is selectively enriched in the internal membranes of late endosomes (LEs), where it participates in the trafficking of proteins and lipids, particularly cholesterol, through this organelle (6)(7)(8). In addition, BMP is involved in the formation of the multivesicular membranes characteristic of the LE (9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…7 Our studies in both murine and human macrophages showed that endosomal accumulation of anti-BMP antibody altered cholesterol distribution in relation to reduced cholesterol efflux to HDL. 8 Most human and animal cells or tissues contain relatively low amounts of BMP, not exceeding 1% to 2% of total phospholipids. However, the level of BMP was shown to dramatically increase in certain inherited lysosomal storage disorders, a group of diseases characterized by endolysosomal lipidosis, such as Niemann-Pick (NP) and Gaucher diseases.…”
mentioning
confidence: 99%